2007
DOI: 10.1007/bf03404320
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pneumococcal Infections in Canadian Children, 1998–2003 Implications for New Vaccination Programs

Abstract: Background: We conducted active surveillance for invasive pneumococcal disease to assess the serotype and antibiotic resistance patterns in Canada prior to universal infant immunization programs, in most provinces. Methods: Active surveillance was conducted by the 12 centres of the Canadian Paediatric Society's Immunization Monitoring Program, Active (IMPACT). This report includes children 16 years of age and younger with S. pneumoniae isolated from a normally sterile site, in 1998-2003.Results: During six yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To our knowledge, this is the only epidemiological study that addresses the incidence of pneumococcal disease in children under 5 years in the UAE. In North America, the reported incidence rates are 72/100 000 in southern California and 11.8-16.1 population in Canada 1213. In Europe, the rates are 42.1 in Great Britain, 24.2 in Finland, and 10.1 population in Germany 1416.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the only epidemiological study that addresses the incidence of pneumococcal disease in children under 5 years in the UAE. In North America, the reported incidence rates are 72/100 000 in southern California and 11.8-16.1 population in Canada 1213. In Europe, the rates are 42.1 in Great Britain, 24.2 in Finland, and 10.1 population in Germany 1416.…”
Section: Discussionmentioning
confidence: 99%
“…In North America, the reported incidence rates are 72/100 000 in southern California and 11.8-16.1 population in Canada. 12 13 In Europe, the rates are 42.1 in Great Britain, 24.2 in Finland, and 10.1 population in Germany. 14 16 In Australia, it is 12.7.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the standard and alternative MLST primers was carried out on five randomly selected isolates from strains collected provided by the Canadian Immunization Monitoring Program ACTive (IMPACT) [ 23 - 26 ]. Isolates were obtained from patients aged 0 – 16 presenting with invasive pneumococcal infection at tertiary care centres across Canada; diagnosis was confirmed by positive S. pneumoniae culture from normally sterile body fluid (blood/cerebrospinal fluid).…”
Section: Methodsmentioning
confidence: 99%
“…However, the prevalence with which the serotypes are recovered from patients with invasive disease varies considerably, presumably because some serotypes have a much greater propensity to cause invasive disease than others. International pneumococcal surveillance has demonstrated that 70–88% of invasive pneumococcal disease in young children was caused by serotypes now included in the seven‐valent protein‐conjugated vaccine formulation (4, 6B, 9V, 14, 18C, 19F, and 23F) (Henriques et al ., 2000; Hausdorff et al ., 2005; Bettinger et al ., 2007). This finding is consistent with the hypothesis that, regardless of ethnic and socioeconomic differences, ‘commonly invasive’ serotypes as a group have a high level of intrinsic virulence relative to other serotypes.…”
mentioning
confidence: 99%